2000
DOI: 10.1182/blood.v96.9.3064
|View full text |Cite
|
Sign up to set email alerts
|

Platelet release of trimolecular complex components MT1-MMP/TIMP2/MMP2: involvement in MMP2 activation and platelet aggregation

Abstract: Matrix metalloproteinase 2 (MMP2) has been reported to be secreted by collagen-stimulated platelets, and active MMP2 has been shown to play a role in platelet aggregation. It has been demonstrated that MMP2 activation is dependent on the complex (membrane type 1 [MT1]-MMP/tissue inhibitor of MMP2 [TIMP2]) receptor and MMP2. We have investigated human platelets as a possible source of MT1-MMP, and we have studied its role in MMP2 activation and in platelet aggregation. Gelatin zymograms showed the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 40 publications
0
69
0
Order By: Relevance
“…Metformin also inhibited MMP‐2 expression in a dose‐dependent manner (Figure 2D). Because MMP‐9 activity is tightly regulated by endogenous inhibitors, that is, tissue inhibitors of metalloproteinase (TIMPs) (Kazes et al ., 2000), we further examined the expression level of TIMP‐1 and ‐2 by semi‐quantitative RT–PCR, but their expression remained essentially unchanged by treatment with metformin (Figure 2E). These results indicate that the lack of effect of metformin on RNA levels for TIMP‐1 and ‐2 may also contribute to suppression of cell invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin also inhibited MMP‐2 expression in a dose‐dependent manner (Figure 2D). Because MMP‐9 activity is tightly regulated by endogenous inhibitors, that is, tissue inhibitors of metalloproteinase (TIMPs) (Kazes et al ., 2000), we further examined the expression level of TIMP‐1 and ‐2 by semi‐quantitative RT–PCR, but their expression remained essentially unchanged by treatment with metformin (Figure 2E). These results indicate that the lack of effect of metformin on RNA levels for TIMP‐1 and ‐2 may also contribute to suppression of cell invasion.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which MMP‐2 is activated at the surface of cancer cells is fully dependent on the activity of MT1‐MMP ( Sato et al , 1994 ; Strongin et al , 1995 ). Recently, Kazes et al (2000) showed that resting platelets express the latent form of MT1‐MMP on their surface and this is activated during collagen‐induced platelet aggregation. The authors hypothesized that MT1‐MMP may contribute to collagen‐induced platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that in addition to embryonic development, morphogenesis, physiological and pathological remodelling, MMPs also act as signalling molecules regulating processes such as vascular reactivity, leukocyte activation and platelet function (Sternlicht & Werb, 2001; Jurasz et al , 2002 ). Indeed, we and others have previously described novel pathways of platelet aggregation that are mediated via the release of matrix metalloproteinase‐1 (MMP‐1) and MMP‐2 from platelets ( Sawicki et al , 1997 ; Sawicki et al , 1998 ; Kazes et al , 2000 ; Martinez et al , 2001 ; Radomski et al , 2001 ; Chung et al , 2002 ; Galt et al , 2002 ; Jurasz et al , 2002 ). Interestingly, MMP‐2 release from platelets and cancer cells stimulates TCIPA ( Jurasz et al , 2001a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets also express MMP‐14, which has a transmembrane domain and is often found in complex with pro‐MMP‐2 and an associated inhibitor, tissue inhibitor of metalloproteinase (TIMP)‐2 . Whether MMP‐9 is produced by platelets or originates from external sources and simply binds to platelets remains a matter of some conjecture, and the anti‐aggregatory effects of MMP‐9 on platelets remain to be elucidated.…”
Section: Platelet‐associated Mmps—location Of Platelet‐associated Mmpmentioning
confidence: 99%